Cytomorphological and Biochemical Profile of Serous Effusions: A Cross-Sectional Study at a Tertiary Care Center in Chitwan, Nepal - Goyal, Binita; Shrestha, Akshunna Rup (Journal of Bharatpur Hospital, 2026)
Background Serous effusions are frequently encountered clinical conditions with diverse non-neoplastic and neoplastic causes, often indicating advanced disease in malignancy. Their evaluation is important for both diagnostic and prognostic purposes. This study aimed to assess protein concentration, classify effusions as transudates or exudates, and correlate these findings with cytomorphological features. Methods A hospital-based cross-sectional study was conducted at the Department of Central Clinical Laboratory, College of Medical Sciences-Teaching Hospital, Bharatpur, Nepal, including 96 serous effusion samples collected from June to August 2023. Total protein and cell counts were measured, and cytological evaluation was performed using standard staining techniques. Data were analyzed using SPSS version 16 with descriptive statistics, Pearson’s correlation, and Mann-Whitney U test, considering p < 0.05 as statistically significant. Results Of the 96 samples, 52 (54.2%) were peritoneal, 43 (44.8%) pleural, and 1 (1.0%) pericardial fluid. Total protein ranged from 0.06 to 5.96 g/dl (mean ± SD: 2.65 ± 1.03 g/dl), with 42 (43.8%) exudates and 54 (56.2%) transudates. Total cell count ranged from 10 to 22,720 cells/cu mm and showed a significant positive correlation with total protein (r = 0.525, p < 0.001). Exudates had significantly higher total protein, total cell count, and neutrophil percentage. Most cases (96.9%) were negative for malignancy, with three exudative cases showing atypia, suspicion, or malignancy. Conclusions Biochemical and cytomorphological evaluation plays a crucial role in diagnosing serous effusions, with malignant effusions typically presenting as exudates. However, cytological assessment should be guided by both fluid characteristics and clinical context for accurate diagnosis.